Um panorma de argumentação de alunos da educação básica: O caso do fatorial - Leandro, Ednaldo José (2006)
This work focuses on the mathematical object factorial. It is part of the project Argumentation and Proof in School Mathematics (AprovaME), which involves a survey of the conceptions of Brazilian students. For this survey, two questionnaires were developed, one related to the domain of algebra and the other geometry and administered to a sample composed of 2012 students aged between 14 and 16 years, studying in the 8th grade or the 1st year of High School of schools located in the state of São Paulo. The questions analyzed for this study were included in the algebra questionnaire. Following a descriptive analysis of the data collected, which indicated that the students had considerable difficulties in constructing valid mathematical arguments, the data set was subjected to a multidimensional analysis using the software CHIC. The results obtained from this analysis evidenced three distinct groups of students within the sample: those who were unable to respond to questions involving the notion of factorial; students who privileged the use of numeric calculations in their responses; and students who focused on the properties of the factorial in constructing their justifications. It was also possible to identify those students whose response profiles most contributed to the formation of these groups. In a second phase of analysis, some of these students were interviews in order to obtain additional data related to factors motivating their responses. In this phase the questionnaire was also administered to mathematics teachers in schools that made up the sample. In general, the results, both quantitative and qualitative, suggest that the question of argumentation and proof, at least in relation to multiplication and division, is not being contemplated with these students. Calculations were the principle tools used by those who managed to respond to the questions and few students were able to justify their responses using mathematical properties, such as, for example, referring to the inverse relationship between multiplication and division